The Stability of the Bali’s Rabies Virus Molecular Marker for the Development of Diagnostic Method - Putu Dimas Abiyoga; Gusti Ayu Yuniati Kencana; I Nyoman Dibia (Udayana University, 2015)
The objectives of this study were to prove that the molecular marker of Bali’s rabies virus is still conserveand to develop a diagnostic method based on molecular marker. Thirty brain samples of dog that had beeninfected by a rabies virus from 2014 and 2015 were used for this research. The sequences of nucleotidewhich were obtained and the sequences of nucleotide accessed in GenBank were analyzed using MEGA5.2 software. The result provided that the specific amino acid (isoleusin) at position 308 (open readingframe) as a molecular marker of Bali’s rabies virus was still conserve. Fragment of N gene amplified byReverse RT-PCR method with a specifically designed primers showed that every isolate of rabies virus hadit’s own typical band, and could distinguish Bali isolate from the others in Indonesia.